Syndrome of increased epithelial permeability in clinical practice. Multidisciplinary national Consensus - V. I. Simanenkov; I. V. Maev; O. N. Tkacheva; S. A. Alekseenko; D. N. Andreev; D. S. Bordin; T. D. Vlasov; N. M. Vorobyeva; V. Grinevich; I. V. Gubonina; M. Yu. Drobizhev; N. S. Efremov; et al. (Кардиоваскулярная терапия и профилактика, 2021)
The purpose of the first multidisciplinary Consensus: to comprehensively analyze the pathophysiological, clinical, and pharmacotherapeutic aspects of the syndrome of increased epithelial permeability (SPEP) as one of the basic mechanisms of the development of human pathology.The Consensus presents the structure of the three main levels of cytoprotection: preepithelial, epithelial and subepithelial, and the structure of intercellular tight contacts in epithelial tissues and endothelium is considered in detail. The clinical sections of the Consensus are devoted to the role of SPEP in diseases of the digestive system, cardio-cardio-vascular and other visceral systems. A separate section summarizes the materials illustrating the significant role of SPEP in mental disorders and diseases of the nervous system.A separate chapter of the Consensus is devoted to cytoprotective therapy in SPEP. Cytoprotective effects of such proton pump inhibitor as rabeprazole, bismuth preparations and probiotics have been shown. Special attention is paid to the clinical and pharmacological specialties of the cytoprotector of rebamipide. Clinical the effectiveness of re-bamipide shown as in functional, so in organic lesions of the digestive system. Its anti-cancer preventive effects are of practical importance.